2019
DOI: 10.1016/j.waojou.2019.100048
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactam allergy in Chinese patients and factors predicting genuine allergy

Abstract: IntroductionBeta-lactams (BL) are the most frequently reported drug allergy, but the vast majority of patients are found not to be genuinely allergic after evaluation. Few studies have investigated the clinical predictors of genuine BL allergy, and the prevalence in hospitalized Chinese patients is unknown.MethodsPatients admitted to a tertiary hospital in Hong Kong (HK) were analyzed to identify the prevalence and factors associated with the presence of BL allergy labels among hospitalized Chinese patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Most self-reports of β-lactam antibiotic allergies are known to be false, and the pilot study found that after testing only approximately 10% of such reports were true allergies. 8 If the rate of misreported allergies were true, more than 7200 patients may need an evaluation for potentially misreported new β-lactam antibiotic allergies in 2018 alone. This variability has substantial implications for skin testing methods and allergy practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most self-reports of β-lactam antibiotic allergies are known to be false, and the pilot study found that after testing only approximately 10% of such reports were true allergies. 8 If the rate of misreported allergies were true, more than 7200 patients may need an evaluation for potentially misreported new β-lactam antibiotic allergies in 2018 alone. This variability has substantial implications for skin testing methods and allergy practices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other centers should analyze the underreported incidence (rather than solely the prevalence) of new drug allergies in other populations.Sensitization patterns among patients with β-lactam antibiotic allergy vary across different regions and ethnicities, which may be attributed to different prescribing practices and possible genetic or geographic predispositions. Regional variations in sensitization patterns have been well reported in non-Chinese populations, and substantial variability across different cohorts was found 8.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Drug allergy is an immunologically mediated DHR that should not be confused with intolerance or side effect that is pharmacologically mediated [ 6 ]. For example, less than 15% of patients with reported beta-lactam allergies were found to have genuine allergy after evaluation, which is similar to western cohorts [ 4 ]. A good understanding of the pathomechanism of an adverse drug reaction is therefore crucial in the correct labelling of a patient's reaction as this has significant implications in clinical management, from choice of appropriate antibiotics to prevention of a catastrophic outcome due to re-exposure [ 7 ].…”
Section: Introductionmentioning
confidence: 91%
“…The prevalence of physician-reported drug allergies is 7.1% based on population-wide studies in Hong Kong [ 3 ]. Up to 14% of hospitalised patients have drug allergy labels [ 4 ]. The incidence of drug allergy or drug hypersensitivity reaction (DHR) has been reported to occur in 4.2 per 1,000 hospitalisations, based on a prospective large Asian cohort studies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%